(untitled) (Current Problems in Rail Vehicles, 2021)
At the beginning, paper briefly describes history of EMU and double deck push-pull trainsets produced at Škoda Vagonka (former Vagonka Studénka). Follows the description of coaches for double deck push-pull trainsets for Czech Railways (ČD). In the second half of 2021, these coaches undergo type-testing process.